Visual impairment, eye diseases, and dementia risk: a systematic review and meta-analysis - Kuźma, E; Littlejohns, TJ; Khawaja, AP; Llewellyn, DJ; Ukoumunne, OC; Thiem, U (IOS Press, 2021)
Background: Visual impairment and eye diseases have been associated with dementia, though with mixed findings and often in cross-sectional studies.